2019
DOI: 10.1038/s41467-019-10921-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation and impact of co-segregated atoms in magnesium having multiple alloying elements

Abstract: Modern engineering alloys contain multiple alloying elements, but their direct observation when segregated at the atomic scale is challenging because segregation is susceptible to electron beam damage. This is very severe for magnesium alloys, especially when solute atoms segregate to form single atomic columns. Here we show that we can image segregation in magnesium alloys with atomic-resolution X-ray dispersive spectroscopy at a much lower electron voltage. We report a co-segregation pattern at twin boundari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 39 publications
3
47
0
Order By: Relevance
“…Recent studies suggested that there are other mechanisms in generating an I 1 fault. One mechanism involves nucleation or formation of twinning disconnections of a single-or three-layer height on a fully coherent 10 11 È É [5] or 10 12 È É [6] twin boundary, as illustrated in Figure 4. For this mechanism, one end of the I 1 fault is an interfacial defect in the twin boundary, while the other end can be a Frank partial, if it terminates inside the twin, or bounded by another interfacial defect in the other side of the twin boundary, if it terminates at the twin boundary.…”
Section: A Dislocations and Stacking Faultsmentioning
confidence: 99%
“…Recent studies suggested that there are other mechanisms in generating an I 1 fault. One mechanism involves nucleation or formation of twinning disconnections of a single-or three-layer height on a fully coherent 10 11 È É [5] or 10 12 È É [6] twin boundary, as illustrated in Figure 4. For this mechanism, one end of the I 1 fault is an interfacial defect in the twin boundary, while the other end can be a Frank partial, if it terminates inside the twin, or bounded by another interfacial defect in the other side of the twin boundary, if it terminates at the twin boundary.…”
Section: A Dislocations and Stacking Faultsmentioning
confidence: 99%
“…We have neither experimental evidence of ITGBs in pure Mg, nor that of SF-I 2 and steps in our Mg-Gd alloy samples. Nevertheless, SFs in CTBs have been observed in an Mg-Nd-Ag alloy [17]. Our proposed SF-I 2 assisted formation mechanism of ITGBs awaits further experimental verification.…”
Section: Resultsmentioning
confidence: 74%
“…It is also doubted if segregated solutes could influence the stability of ITGBs, as much as previously manifested for CTBs in Ref. [6,17]. The biggest challenge to these puzzles is the experimental analytical difficulty to solve accurately the low-symmetry ITGB structures.…”
Section: Introductionmentioning
confidence: 96%
“…Accordingly, the effects of those solute atoms on the ESF, EWF, dislocation width, bonding structures, twinnability, and ideal strength are comprehensively studied [93,95,100]. Similarly, recent works have reported segregations and twin boundary pinning to strengthen Mg alloys [102,103]. Moreover, lattice strain engineering has been considered as a key strategy in discovering advanced materials.…”
Section: Mg Alloysmentioning
confidence: 99%